PREVALENCE OF HEPATITIS G VIRUS AMONG PATIENTS WITH CHRONIC LIVER DISEASE AND HEALTHY INDIVIDUALS, SANA'A CITY-YEMEN - Saad Al-Dabis, Esmail Mohammed; Al-Shamahy, Hassan A.; Al-Hadad, Maria Mansour Saeed; Al-Shamahi, Emad Hassan (Universal Journal of Pharmaceutical Research, 2019)
Objective: Hepatitis G virus (HGV) is a newly discovered and enveloped RNA positive-stranded flavivirus-like particle, which has not yet been proven to have major negative effects on liver. Therefore, it is important to estimate the prevalence and risk factors of hepatitis G virus infection in Yemeni viral hepatitis patients and general population to design standard prevention and treatment plans. Methods: Screening HGV antibodies among 60 chronic HBV and 144 chronic HCV patients comparing with its prevalence in 218 healthy controls were carried out. Serum samples were collected and tested for human HGV IgG by commercially available ELISA technique. Demographic data such as gender, age, and risk factors of contracting HGV virus were recorded in predesigned questionnaire. Results: The crude prevalence rate of HGV was 2.8%, female specific rate was 0% and male specific rate was 3.5%. The prevalence of HGV among HBV patients was 0%; HCV was 1.4% while in healthy individuals it was 4.6%. When age groups considered, the prevalence of HGV among age groups 20-29 years and 30-39 years was 3.5%, while in older age groups the rate of HGV was 0%. There was a trend towards increased levels of HGV infection with the second and third decades of life (3.5%). There was no significant association between HGV infection and risk factors of hepatitis viruses. Conclusion: It can be concluded from this study that HGV virus is circulating in the risk groups and in the community in general Yemen, and there is a possibility that this virus may at some time become epidemic if preventive measures are not applied. The risk of community among healthy people more than in risk groups as HBV and HCV patients. Additionally HGV increases with young male adults. Peer Review History: Received 6 October 2018; Revised 7 November; Accepted 13 December; Available online 15 January 2019 Academic Editor: Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com Reviewer(s) detail: Antonio José de Jesus Evangelista , Federal University of Ceará, UFC, Brazil, tony_biomed@hotmail.com Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com